2013
DOI: 10.1179/1351000213y.0000000062
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide concentrations in gas emanating from the tails of obese rats

Abstract: This study was undertaken to investigate the effects of oral L-arginine administration and exercising training on the NO concentration emanating from rat tail and NOx in plasma. Obese (fa/fa) Zucker rats (n = 22) were divided into four groups: (1) oral L-arginine administration (A) (n = 6), (2) exercise training (E), (3) exercise training + L-arginine administration (E + A) (n = 5), and (4) non-exercise training + non-L-arginine administration (N) (n = 6). The control (+/+) Zucker rats (n = 22) were also divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…The same group later reported that serum levels of caffeine and nine of its downstream metabolites were decreased, which was irrelevant to total caffeine intake or disease severity [9]. We also reported by mass spectrometry that the ratio of serum tyrosine to phenylalanine was less than 0.82 in 49% of PD patients, but in none of controls [10]. Trivedi et al recently reported that perillic aldehyde and eicosane were increased in sebum samples collected from the upper back in PD [11].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…The same group later reported that serum levels of caffeine and nine of its downstream metabolites were decreased, which was irrelevant to total caffeine intake or disease severity [9]. We also reported by mass spectrometry that the ratio of serum tyrosine to phenylalanine was less than 0.82 in 49% of PD patients, but in none of controls [10]. Trivedi et al recently reported that perillic aldehyde and eicosane were increased in sebum samples collected from the upper back in PD [11].…”
Section: Introductionmentioning
confidence: 54%
“…According to our personal experiences, breath gas is largely influenced by volatile substances produced or consumed by oral microbiota, whereas the skin gas is devoid of these factors. Although acquisition of the skin gas was more tedious than that of breath gas, we previously developed a method to reproducibly obtain gas samples from the skin [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“… 69 On the other hand, no significant differences in serum nitric oxide concentrations were observed between groups, which is in agreement with a previous study that demonstrated no change in the level of plasma nitric oxide after 4 weeks of moderate intensity exercise in Zucker obese rats. 103 Results of this study showed that sedentary behavior, LIT, and HIIT had no effect on inflammatory and oxidative stress markers. However, because this is the first study to examine the influence of an HFHC diet with different intensities of PA on markers of inflammation and oxidative stress, more research is required to fully understand these results.…”
Section: Discussionmentioning
confidence: 70%